Integration of a service-learning component into a course on nursing care for children with developmental disorders: A mixed-methods study. (June 2022) - Chao, Kuo-Yu; Yang, Bao-Huan
Abstract: Background: Service-learning provides nursing students with hands-on experience in a real-world setting. Students learn how to care for others and manage their emotions. Aim: This study examined the effectiveness of integrating service-learning into a nursing course on nursing care for children with developmental disorders. Design: This was a mixed-methods study with two pretest-posttest quantitative analyses and a qualitative component. Methods: Nursing students ( N  = 74) enrolled in a semester-long course in nursing care for children with developmental disorders participated in the study. Data were collected between February 2017 and June 2021. The service-learning part of the course assigned teams of two to three students to provide nursing care for a child (ages 5–19 years) diagnosed with a developmental disorder. At the conclusion of the course, students presented a short video with reflections of their experiences. Pretest versus post-test scores compared mid-term and final exam scores regarding knowledge of children with developmental disorders and scores on a 9-item self-report instrument on service-learning skills. Self-reflections from the video presentation provided qualitative data about the impact on students' awareness of the caregiving needs of children with developmental disorders. Results: The mean final exam scores were significantly higher compared with midterm scores (96.12, (SD = 4.63) vs 94.82 (SD = 12.08); F = 6.81, p  < .001), indicating knowledge of developmental disabilities had increased. Pretest vs posttest scores for service-learning skills indicated confidence had significantly increased ( p  < .001). Students' video reports indicated sensitivity to the challenges and needs of these children had increased. Conclusions: Service-learning exposed nursing students to the challenges and rewards of caring for children with developmental disorders. Knowledge, as well as confidence, increased. Nurse educators could easily integrate service-learning into courses required as part of the curriculum for pediatric nursing students. Highlights: Service-learning (SL) provides nursing students hands-on experience. SL was integrated into a course on children with developmental disorders. The SL component reinforced, and augmented knowledge gained in the classroom. SL exposed students to challenges and rewards of caring for these children. Nurse educators should include a SL component in the pediatric nursing curriculum.